2010
DOI: 10.7150/ijbs.6.556
|View full text |Cite
|
Sign up to set email alerts
|

Activity and interactions of antibiotic and phytochemical combinations against Pseudomonas aeruginosa in vitro

Abstract: In this study the in vitro activities of seven antibiotics (ciprofloxacin, ceftazidime, tetracycline, trimethoprim, sulfamethoxazole, polymyxin B and piperacillin) and six phytochemicals (protocatechuic acid, gallic acid, ellagic acid, rutin, berberine and myricetin) against five P. aeruginosa isolates, alone and in combination are evaluated. All the phytochemicals under investigation demonstrate potential inhibitory activity against P. aeruginosa. The combinations of sulfamethoxazole plus protocatechuic acid,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
122
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 192 publications
(135 citation statements)
references
References 47 publications
11
122
0
2
Order By: Relevance
“…The antipseudomonas activity of BEB has been revealed to be rather weak (MIC≥512 µg/ml) (14,17). In accordance with this, the present study also found a relatively high MIC of BEB in P. aeruginosa.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…The antipseudomonas activity of BEB has been revealed to be rather weak (MIC≥512 µg/ml) (14,17). In accordance with this, the present study also found a relatively high MIC of BEB in P. aeruginosa.…”
Section: Discussionsupporting
confidence: 79%
“…The initial PA012 suspension (1x10 5 CFU/ml) was incubated with BEB and/or IMP at their concentrations at which synergism had been previously determined by using the checkerboard assay (17). The cells were counted at the designated time-points (0, 4, 8, 12 and 24 h).…”
Section: Time-kill (T-k) Testmentioning
confidence: 99%
See 1 more Smart Citation
“…22 We have previously shown that dietary phenolic compounds are effective against the intracellular bacterium C. pneumoniae. 17,18 As it has been proposed that natural compounds in combination with antibiotics could be a new strategy for developing therapies for infections caused by bacterial species and that natural plant products can potentiate the activity of antibiotics in combination, 23,24 we wanted to investigate whether coadministration of phenolic compounds with the antichlamydial compound doxycycline results in synergistic inhibition of acute C. pneumoniae infection. The combinations of natural phenols and doxycycline did not improve Interaction indices, inhibition percentage of C. pneumoniae growth in parenthesis, and host cell viability percentages in square brackets, are presented.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have showed that phytochemicals can potentiate the activity of eradicating biofilm of antibiotics in combination (46)(47)(48)(49). The combinations of antibiotic sulfamethoxazole with protocatechuic acid/ellagic acid/gallic acid and tetracycline with gallic acid, cefoperazone with allicin showed synergistic mode of interaction and were highly effective in inhibition P. aeruginosa biofilm under in vitro conditions (50). Vitexin has been found to potentiate the anti-biofilm activity of azithromycin and gentamicin on P. aeruginosa (51).…”
Section: Discussionmentioning
confidence: 95%